An Alternative Explanation of the Price Puzzle - Paolo Giordani (Sveriges Riksbank, 2001)
This paper proposes a simple explanation for the frequent appearance of a price puzzle in VARs designed for monetary policy analysis. It suggests that the best method of solving the puzzle implies a close connection between theory and empirics rather than the introduction of a commodity price. It proves that the omission of a measure of output gap (or potential output) spuriously produces a price puzzle in a wide class of commonly used models. This can happen even if the model admits a triangular identification and if the forecasts produced by the misspecified VAR are optimal. In the framework of a model due to Svensson, the omission of a measure of output gap is shown to generate several other incorrect conclusions. When the model is tested on US data, all predictions are supported.
Keywords: E30; E52; 330; VAR; monetary policy; misspecification; output gap; technology shocks.